ZnO Nanomaterials: Current Advancements in Antibacterial Mechanisms and Applications - Jiang, Shengjie; Lin, Kaili; Cai, Ming (Frontiers in Chemistry, 2020)
The prevalence of various diseases caused by bacteria has been increasing, and some traditional antibiotics have been reported to have varying degrees of resistance. ZnO nanomaterials (ZnO-NMs), due to their excellent broad-spectrum antibacterial properties, lasting antibacterial effects, and excellent biocompatibility, have quickly become the research focus of new antibacterial agents. While the narrow light response range of ZnO-NMs has limited the antibacterial performance to some extent, and modifying it by various means to improve its response under visible light, such as doping metal/nonmetal atoms, depositing noble metals and coupling carbon materials, which is a recent research hotspot. Herein, the current mainstream claims about the antibacterial mechanisms and applications of ZnO-NMs are reviewed. Moreover, the limitations of ZnO-NMs that still exist and the developing trends in the future are also discussed.